My math teacher said: I provided you with an already simplified expression. Your task is to create two expressions (for each) that would simplify the given expression.

3x - 19
-11y + 6
25h - 42
62w + 80
-17b + 1

Respuesta :

Answer:

1. (4 x  - 20) - (x +  1 )  = 3 x - 19

2. (-6 y  + 3) + (-5 y  +  3 )  = -11 y + 6  

3. (15 h  - 50) + (10 h  +  8)  = 25 h - 42

4. (60 w + 40) + (2 w  +  40)  = 62 w + 80

5. (20 b   + 10) - (37 b + 9 )  =-17 b + 1

Step-by-step explanation:

The one good way to simplify the given expression is to break the TERMS from all the given terms and take it out of the given expression.

(a) 3 x - 19  

Here, two expressions that on simplification gives   3 x - 19   are A  - B

Here A  = 4 x  - 20 , B = x +  1

A - B = (4 x  - 20) - (x +  1 )  = 3 x - 19

(b) -11 y + 6

Here, two expressions that on simplification gives    -11 y + 6   are A + B

Here A  = -6 y  + 3 , B = -5 y  +  3

A + B = (-6 y  + 3) + (-5 y  +  3 )  = -11 y + 6  

(c) 25 h - 42

Here, two expressions that on simplification gives  25 h - 42   are A + B

Here A  = 15 h  - 50 , B = 10 h  +  8

A + B = (15 h  - 50) + (10 h  +  8)  = 25 h - 42

(d) 62 w + 80

Here, two expressions that on simplification gives  62 w + 80   are A + B

Here A  = 60 w + 40 , B =  2 w  +  40

A + B = (60 w + 40) + (2 w  +  40)  = 62 w + 80

(e) -17 b + 1

Here, two expressions that on simplification gives   3 x - 19   are A  - B

Here A  = 20 b   + 10 , B = 37 b - 9

A - B = (20 b   + 10) - (37 b + 9 )  =-17 b + 1

Here, there MANY WAYS TO DO THIS , i am just giving one.